Understanding English Language Teachers' (De)motivation Toward Continuing Professional Development Through Psychological Contract and Work Attitude - Acar, Sonay Ezel; Erozan, Fatos (Sage Publications Inc, 2024)
Motivation as the driving force for achieving success, pursuing goals and fulfilling objectives, is shaped and affected by intrinsic and extrinsic factors, psychological contract and work attitude. Like other professionals, English language teachers also need to be motivated for continuous professional improvement in order to achieve organizational goals and ultimately reach high educational quality. Thus, it is of high importance to investigate teachers' (de)motivation toward CPD. This paper focuses on the (de)motivational reasons as to why English language teachers at a university do not take part in professional development despite their awareness of its significance for their career, institution's development and their students' learning. The data from EFL teachers were collected through an online questionnaire consisting of three open-ended questions. The majority of the teachers were found to feel that the continuing professional development events were organized without considering their current workload, needs and contextual factors. It was also found out that the general organizational atmosphere and work attitudes of their colleagues led to decreased motivation and psychological contract. These results offer certain implications for the administrators of educational institutions regarding the importance of considering motivational factors, psychological contract and work attitude in planning continuing professional development for English language teachers. This paper focuses on the (de)motivational reasons as to why English language teachers at a university do not take part in professional development despite their awareness of its significance for their career, institution's development and their students' learning. The data from 30 English language teachers were collected through an online questionnaire consisting of three open-ended questions. According to the findings, the majority of the teachers feel that the continuing professional development events were organized without considering their current workload, needs and contextual factors. It was also found out that despite a group of teachers being motivated, the general organizational atmosphere and work attitudes of their colleagues led to decreased motivation and psychological contract. These results offer certain implications for the administrators of educational institutions of the same type regarding the importance of considering motivational factors, psychological contract and work attitude in planning continuing professional development for English language teachers.
Keywords: continuing professional development; (de)motivation; English language teachers; psychological contract; work attitude